Viabilitas Nematoda Entomopatogen Steinernema spp. dalam Media Kombinasi Senyawa Humik - - WAGIYANA; Didik SULISTYANTO; Sugeng WINARSO (Fakultas Pertanian Universitas Jember, 2008)
Its well known, That Entomopathogenic Nematods (EPNs) used as biological agentswhich effective to control pest of Spodoptera litura (Noctuidae: Lepidoptera).The aims of thisresearch were to find out the multifungsion product as well as a biofeltilizer and biopesticide whichsuitable for agriculture sustainability, secondly the materials were to mixed the humic compound andbiological agent Entomopathogenic Nematodes (EPNs). Combination of biopesticide with EPNs asactive ingredient and humic compound as biofertilizer to find out a good product combination whichindicated the highest viability and activity of EPNs Steinernema spp on humic compound, in orderapplication of these meterial more effective and efficient to prepare the soil fertility and pest problem.This research was done with inoculation of EPNs on the medium/culture e.c: phosphate solublebacteria Pseudomonas putida 27.4B, zeolit and the humic compound (liquid culture). Pathogenecitytest of EPNs were done after incubation on the humic compound to the larvae of S. litura.The result of this research showed that long time of viability EPNs only for fourth weeks on the humicculture at (4000 ppm). Actually the EPNs from this incubation could 100 % mortality of the S. lituralarvae after 72 hours inoculation. The infection rate of EPNs on the larvae S. litura was 30,3 tailsduring 24 hours incubation. The viability of EPNs Steinernema spp on the medium with 1000 ppmhumic compound was 20 % after 120 hours and after 4 weeks later all EPNs could not survive on thismedium. It seems, the medium containing zeolith, P. putida 27.4B and humic compound at 1000 ppmwas not suitable medium neither for nematods growth or larvae S. litura survival.